الأمن الثقافي كدعامة أساسية لبناء أمن المجتمعات الإنسانية قراءة في الأمن الهوياتي العربي - عمران وفاء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يعاني الواقع العربي من مخاطر متعددة تهدد أمنه الثقافي فإلى جانب أن الثقافة في وطننا العربي تتكبد الهجمات و محاولات التسلل من التيارات المعادية فإنها تعاني الضعف و قصور على مستوى بناء الهوية والشخصية الإسلامية والحفاظ عليها، و خاصة ما تعلق بلسانهم العربي الفصيح ولغتهم الأم ، لغة القرآن و جراء هذا اللاوعي بقدر هذا الزلل تخرق أولى دعائم الأمن الثقافي والهوية العربية بالمساس بأبجديات الخطاب الثقافي. The Arab reality suffers from multiple threats to its cultural security. Besides the fact that culture in our Arab homeland incurs attacks and attempts to infiltrate hostile currents, it suffers from weakness and inadequacy in the construction and preservation of Islamic identity and personality. and, especially, those relating to their eloquent Arabic tongue and mother tongue, The language of the Qur ’an and because of this unconsciousness as much as this slippage violates the first pillars of cultural security and Arab identity by compromising the alphabets of cultural discourse.